LEVEL OF KNOWLEDGE AND MOTIVATION ON THE USE DENTURES BY PEOPLE WHO LOSE TEETH IN PUSAKA RAKYAT VILLAGE BEKASI - Marsigid, Didik; Mujiwati; Alpadari, Iin (Journal of Vocational Health Studies, 2023)
Background: Tooth loss is condition in which a tooth falls out of the socket or out of place. Missing teeth that aren't replaced immediately can interfere with mastication, and Temporomandibular Joint (TMJ) disorder. Using dentures is one of the right ways to deal with missing teeth, but not everyone wants to replace missing teeth with dentures. Low use of dentures is influenced by level of knowledge and motivation of individuals in meeting denture needs. Several factors that influence level of knowledge and motivation are age, gender, education level, occupation, and income. Purpose: To determine level of knowledge and motivation toward use of dentures by people who have lost their teeth in Pusaka Rakyat Village, Tarumajaya District, Bekasi Regency. Method: Quantitative descriptive with sample 100 people, has criteria including people in Pusaka Rakyat Village who are 20 years old, have lost at least one tooth element, and never used dentures. Data collection was carried out in February-April 2021 by filling questionnaires by respondents. Result: Chi-Square test with significance p-value<0.05 found significant relationship between age and level of knowledge and occupation with motivation to use dentures. Conclusion: Age and occupation are very influential on a person's motivation and motivation is very influential on a person's income, so they will be more aware about dentures.